Training To Improve The Promotion Capability Of MSMEs In Wingko Babat Village By Utilizing Smart Technology - Andy Rachman; Faza Wahmuda; Muchamad Kurnaiwan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The development of information technology from year to year is increasing. This technological development must be followed by every resident in any country, one of which is the people in Indonesia. The use of information technology in Indonesia is carried out by companies, hospitals, governments, schools, and even SMEs. UMKM is an abbreviation for Micro, Small, and Medium Enterprises. UMKM itself is a trading business carried out by the community in a small scope. In Indonesia, there are many MSMEs scattered throughout the region. Various MSMEs currently start in the business sector, services, and even home businesses. One of the home trading businesses managed by homemakers is the WINGKO LA UMKM. WINGKO LA UMKM is a business from Mrs. Yuaningsih in the Lamongan Region, East Java. Two types of Wingko business products from Mrs. Yuaningsih are wet wingko and crispy wingko. In implementing her sales, Mrs. Yuaningsih uses a word-of-mouth sales model and does not use information technology optimally. From this problem, the researchers assisted WINGKO LA and WINGKO sellers in Jl. Sumargo Gg Kenongo and Around Lamongan in the form of information technology training to assist the product sales and promotion process. The technology used by WINGKO Lamongan SMEs includes Instagram, YouTube, Facebook, WhatsApp, TikTok, and Marketplace.